PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI - Irma Daniyati, ; Sri Sudarmini, (Pendidikan Ekonomi, 2012)
The purpose of the study is to ditermine the activities of teachers and students, and to ditermine the learning outcomes of students after implementing  the direct instruction model. Researchers used classroom action research design was achieved in two cycles, The results showed that the activities of teachers and students in direct instruction model is good. Seen from the results of students learning there is an increasing mastery learning classical 10,25 %.